How to Harvest The Free Fibula Flap - Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester; Ralena, Nadhira Anindita (Lingkar Studi Bedah Plastik Foundation, 2020)
Summary: Free fibular flap (FFF) is a composite flap consisting of fibular bone and skin paddle. Muscle may be added to the flap. It has several advantages and disadvantages. The fibular free flap is well suited for any reconstruction of the head and neck. It is suitable for defects of the anterior mandibular arch or lateral defects in patients who wish to undergo osseointegrated dental reconstruction. Meanwhile, its contraindications are related to significant atherosclerotic diseases the patient has or congenital variants of the arteries. Preparations for FFF procedure consist of history taking, physical examinations and supporting examinations, like other free flaps procedure in general. Several intraoperative preparations should also be done.